PENGARUH PERBEDAAN SUHU DAN SUMBER KARBON PADA PERTUMBUHAN Pseudomonas sp. STRAIN LSU20 DALAM MENDESULFURISASI DIBENZOTIOFENA - Iqbal, Muhammad; Wayan Gunam, Ida Bagus; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 3 (2016): September, 2016)
Desulfuriztion of  crude oil to be low sulfur fuel  content  is a  main concern by all researcher. Pseudomonas  sp. strain LSU20 known as one of  bacteria which could degrade  dibenzothiphene (DBT)  on n-tetradecane  (TD) oil model.  Temperature  Growth  condition of this bacteria was experimented  at  37ºC and 45ºC. Some  carbon sources  were also tried in this experiment, such as glucose, sucrose, and citric acid.  Using glucose as source of carbon and temperature growth condition at 37ºC, the bacteria could degrade 67% (DBT) in TD after 96 hours of incubation. In this condition the bacteria growth could reach OD660nm up to 0,978. Key: LSU20, dibenzothiophene, n-tetradecane, biodesulfurization.
Keywords: 101